Collective remembering of Confucianism in Chinese language textbooks: Official historical representations from 1949 to 2019 - Xie T; Chen S; Wang D; Liu JH (SAGE Publishing, 2021)
This study focuses on the collective remembering of an ancient system of meaning, examining content and changes in the construction of Confucianism in Chinese textbooks. The data consists of 84 editions of Chinese language teaching textbooks published by the People’s Education Press from 1949 to 2019. Content analysis shows that Confucianism is and was barely represented in this corpus. Thematic analysis shows that: (i) Only Confucius and Mencius were recognized as Confucian masters. (ii) Representations of Confucianism in the textbooks come from The Analects, Mencius, The Book of Rites, and The Book of Poetry, all of which are more than 2000 years old. (iii) Except for the 1970s, Confucianism was represented in a positive or at least neutral way. (iv) Confucianism is represented in a distant, abstract, decontextualized, and apolitical way, disconnected from students’ daily life. This gives insight into how a core representation stripped of its peripheral elements can lose meaning, and lose its normative influence on behavior. Contributions to collective memory, and implications for how to edit Chinese language textbooks to be more engaging are discussed.
Keywords: collective remembering; social representations; cultural memory; Confucianism; content analysis; thematic analysis